A Rare Case of Adrenal Intravascular Large B-Cell Lymphoma Diagnosed via Percutaneous Needle Biopsy - Jiafei Zeng; Jin Li; Shuai Luo; Jinjing Wang (World Journal of Surgical Oncology)
Abstract Background Intravascular large B-cell lymphoma (IVLBCL) is a rare subtype of diffuse large B-cell lymphoma, predominantly affecting the elderly. The disease often involves multiple tissues and organs, leading to a wide range of nonspecific symptoms. Early detection is challenging due to the absence of prominent signs such as enlarged lymph nodes or significant blood and bone marrow abnormalities in the early stages. Moreover, biopsy specimens may be insufficient for accurate diagnosis, resulting in a high false-negative rate and delayed treatment initiation. Case presentation A 61-year-old male presented with a bilateral adrenal mass detected during routine examination. The patient had a history of diabetes, managed with regular antidiabetic medications and good blood sugar control for over a year. Symptoms included dizziness and mild bilateral flank discomfort. Imaging revealed patchy, soft tissue lesions in both adrenal glands on an upper abdominal CT scan. The larger lesion measured 71 × 37 mm on the left, and 51 × 31 mm on the right. Enhanced imaging showed mild to moderate enhancement, with neoplastic lesions or metastasis suspected. A CT-guided percutaneous biopsy was performed. Histopathological examination revealed large or medium-sized lymphoma-like cells localized to endothelial markers CD31 and CD34-positive lumen epithelium, with strong diffuse positivity for B-lymphocyte markers. The final diagnosis was IVLBCL. The patient was treated with rituximab combined with CHOP chemotherapy and discharged without significant symptoms. Conclusions IVLBCL is often overlooked due to its varied and nonspecific clinical presentation, making early diagnosis difficult. The disease progresses rapidly and has a poor prognosis, with definitive diagnosis relying on pathological findings. Increased awareness of this rare lymphoma is crucial, particularly for diagnosing needle biopsy specimens in patients with mild symptoms and no distinct space-occupying lesions. Careful morphological examination, supported by targeted immunohistochemical staining (for B-cell and endothelial markers), is essential for timely diagnosis.